2020
DOI: 10.1002/cjp2.167
|View full text |Cite
|
Sign up to set email alerts
|

Greater utility of molecular subtype rather than epithelial‐to‐mesenchymal transition (EMT) markers for prognosis in high‐risk non‐muscle‐invasive (HGT1) bladder cancer

Abstract: Approximately 75% of bladder cancers are non-muscle invasive (NMIBC). Of these, up to 53% of cases progress to life-threatening muscle-invasive bladder cancer (MIBC). Patients with high-grade stage T1 (HGT1) NMIBC frequently undergo radical cystectomy (RC), although this represents overtreatment for many. Identification of progressors versus non-progressors could spare unnecessary treatment. Recent studies have confirmed that urothelial carcinoma is composed of two main molecular subtypes, basal and luminal, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…KLK6 was identified as a prognostic gene for MIBC (39). Increased expression of SCUBE2, as a luminal marker of urothelial carcinoma, was found to be significantly associated with better disease-free survival (40). The expression of SERPINB2 was proved incrementally expressed in cisplatin-resistant bladder cancer cell lines (41).…”
Section: Discussionmentioning
confidence: 98%
“…KLK6 was identified as a prognostic gene for MIBC (39). Increased expression of SCUBE2, as a luminal marker of urothelial carcinoma, was found to be significantly associated with better disease-free survival (40). The expression of SERPINB2 was proved incrementally expressed in cisplatin-resistant bladder cancer cell lines (41).…”
Section: Discussionmentioning
confidence: 98%
“…According to distinct clinical recurrence, progression and prognosis, BC is classi ed into non-muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC). Recently, most patients with BC have been diagnosed with NMIBC [4], and approximately 53% experience progression to life-threatening MIBC [17]. Given the very high recurrence rate, the prediction of recurrence is particularly important in NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the cancers with the most longitudinal costs and consumed resources. Approximately 70-75% of newly diagnosed primary bladder cancers are non-muscle-invasive bladder cancer (NMIBC) (Lenis et al, 2020;Ottley et al, 2020). Up to 21-53% of them eventually progress to life-threatening muscle-invasive bladder cancer (MIBC) (Cookson et al, 1997;van den Bosch and Alfred Witjes, 2011), depending on the stage and grade.…”
Section: Introductionmentioning
confidence: 99%
“…They found that both stromal tumor-infiltrating lymphocyte (sTIL) levels in noninvasive papillary urothelial carcinoma areas and increased expression of the luminal markers FOXA1 and SCUBE2 are significantly associated with better disease-free survival (DFS), but no EMT markers showed any trend. They suggested that molecular subtype markers, rather than EMT markers, might be preferable to study biomarkers of HGT1 urothelial carcinoma (Ottley et al, 2020). Rouanne et al focused on stromal lymphocyte infiltration by evaluating the percentage of stromal area infiltrated by mononuclear inflammatory cells over the total intratumoral stromal area (Rouanne et al, 2019).…”
Section: Introductionmentioning
confidence: 99%